Analytical Report on Exhaust Emission Optimization from Logistics & Packing Industries: A Green Logistical Approach - P. Benrajesh; A. John Rajan (Advanced Aspects of Engineering Research Vol. 2, 2021)
Two out of every three clients prefer eco-friendly brands from diet products to travel products and they are also eager to pay more for the service, based on Boston consulting group’s survey. The front interface of any finished product with consumer are: packing design and materials, have to facilitate the common goal of reducing carbon prints. To attain the low carbon emitted packing, a tool designed with policies named as ‘Green packing’. The objective of this article is to determine the high-ranking parameter which can influence the green packing, and to develop the optimum values for designing low emission packing materials. The outcome obtained manifests that material used in packing has larger influence on the green-house gas emission.